Effect of electron collisions on čerenkov radiation from magnetoplasma - Shukla P.K.; Singh R.P.; Singh R.N. (My University, 2025)
The theory of čerenkov radiation from magnetoplasma has been modified to account for the effect of electron collision frequency. The results are compared with the čerenkov theory for collisionless magnetoplasma. The čerenkov radiation in the magnetosphere is unaffected by electron collisions. In the ionosphere the radiated power is found to change by several times as compared to radiation by collisionless magnetoplasma. © 1970 Taylor and Fancis Group, LLC.